2012
DOI: 10.1016/s1473-3099(11)70287-0
|View full text |Cite
|
Sign up to set email alerts
|

Crowd and environmental management during mass gatherings

Abstract: Crowds are a feature of large cities, occurring not only at mass gatherings but also at routine events such as the journey to work. To address extreme crowding, various computer models for crowd movement have been developed in the past decade, and we review these and show how they can be used to identify health and safety issues. State-of-the-art models that simulate the spread of epidemics operate on a population level, but the collection of fine-scale data might enable the development of models for epidemics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 33 publications
1
82
0
3
Order By: Relevance
“…Outbreaks in relation with sport events, Hajj pilgrimage, food festivals, fairs or occurring in the setting of cruise ship, school, restaurant or hotel (including weddings at restaurants or hotels) were excluded because they were reviewed elsewhere [6][7][8].…”
Section: Definition Of Large Scale Open Air Festivalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks in relation with sport events, Hajj pilgrimage, food festivals, fairs or occurring in the setting of cruise ship, school, restaurant or hotel (including weddings at restaurants or hotels) were excluded because they were reviewed elsewhere [6][7][8].…”
Section: Definition Of Large Scale Open Air Festivalsmentioning
confidence: 99%
“…According to a survey conducted in the United Kingdom (UK) during the year 2009, the total number of visits to UK music festivals was estimated to exceed 7.7 million attendees, including overseas and domestic participants combined (www.ukmusic.org/assets/media/UK%20Music%20 -Music%20Tourism.pdf). Music festivals, which may involve as many as 400,000 cumulated attendees, share the usual health risks associated with large MGs, including communicable and non-communicable diseases [6][7][8]. A mean percentage of 1.5% attendees at music festivals seek medical care during these events, and the highest proportion recorded of attendees seeking care was 10% [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It discussed the common diseases found during Hajj period, MOH operation plan at Hajj, the emergence of medicine at Hajj, Non-communicable potential risks of mass gathering Hajj, Infectious disease surveillance at Hajj, hospital infection control, and researchers model of mass gathering medicine and application during Hajj period. [7][8][9][10][11][12][13][14][15] Although few studies discussed medication related issues, for the instant; the report by Al-Tawfiq JA that 84% of pilgrims received antibiotics for upper respiratory tract infection, 17% of Pakistani pilgrims received antibiotics, the most medication during Hajj for prophylaxis Ciprofloxacin. [16] Another study discussed the outpatient services during Hajj at one hospital; they found the most medication prescribed Antibiotics 43.3% followed by an Analgesics and Antipyretic 25.2% and Medication for Ischemic Heart Disease (IHD), Chronic Renal Failure (CRF), and Central nervous system disorder (CNS disorder).…”
Section: Introductionmentioning
confidence: 99%
“…Any of these risks could entail mass casualties. An additional possibility that would involve mass casualties is terrorism 21,22,23 .…”
Section: Discussionmentioning
confidence: 99%